Особистість як духовно-екзистенційна основа людського буття - Гудзенко-Александрук, Олена Георгіївна; Hudzenko-Aleksandruk, Olena H. (Тернопільський національний університет ім. Володимира Гнатюка, 2008)
У статті розглядається особистість як духовне утворення, а також духовно-екзистенційна основа людського буття. Зазначається, що необхідною умовою саморозвитку особистості є самореалізація, яка передбачає її самовдосконалення. The article deals with a personality as a spiritual formation and also as a spiritual-existential foundation of human existence. It is noted that the essential condition for self-development of a personality is its self-realization which presupposes its self-perfection.
A Personality as a Spiritual-Existential Foundation of Human Existence
Keywords: особистість як духовне утворення; духовно-екзистенційна основа людського буття; саморозвиток особистості; самовдосконалення; personality as a spiritual formation; a spiritual-existential foundation of human existence; self-development of a personality; self-perfection